Several low back pain‐related misbeliefs are still around in 2020: A cross‐sectional survey in Belgium. (27th October 2021) - Demoulin, Christophe; Gabriel, Laura; Nève de Mévergnies, Orléane; Henket, Laura; Roussel, Nathalie; Goubert, Liesbet; Vanderthommen, Marc; Pitance, Laurent
Abstract: Background and purpose: Low back pain (LBP)‐related misbeliefs are known to be among risk factors for LBP chronification and for persistence of chronic pain. The main objective of this study was to investigate the current LBP‐related beliefs in the general population in Belgium, considering the fact that the last survey in Belgium about the topic was conducted more than 15 years ago. Methods: A cross‐sectional study design was used. Belgian adults (>17 years old) were recruited in the three regions of the country by means of non‐probabilistic recruitment methods. Participants were invited to fill in a battery of questionnaires including demographic questions as well as questions about their LBP history and the LBP Beliefs Questionnaire (LBPBQ). Results: A total of 3724 individuals participated in the study. The LBPBQ scores indicated several LBP‐related misbeliefs. About 15%–25% of participants still think that imaging tests can always identify the cause of pain and that bed rest is the mainstay of therapy. The majority of the participants think that "unnecessary" movements should be avoided when having LBP (58% of the respondents), and that they should "take it easy" until the pain goes away (69%). Most respondents also had maladaptive/wrong expectations, for example, a systematic worsening with time (65%) and a need for surgery in case of disc herniation (54%). Conclusions: The present study suggests that in 2020 several LBP‐related misbeliefs are still current in Belgium, particularly regarding the vulnerability of the spine. Therefore, further efforts to improve LBP‐related beliefs/knowledge in the general population are necessary.